Interaksi Sosial Masyarakat di Lingkungan Tempat Tinggal Penderita COVID-19 - Muhammad; Ilham Abu; Andi Nikhlani (Jurnal Kebijakan Pembangunan, 2021)
The presence of COVID-19 can affect social interactions among the community, for example limiting themselves and their families to visit family and neighbor which they have been doing so far. This study aims to describe the social interactions that occur in communities where people with COVID-19 live. The design of this research is qualitative based on the social problems faced by the community during the COVID-19 pandemic. Research informants are people who live in RT. 27 Teluk Lerong Ulu Sub-district, Samarinda City and selected 5 people and the head of the local RT as key informants who could provide the necessary information through purposive sampling. Data collection techniques through interviews with informants and key informants using interview guidelines, observation and documentation. This research was conducted in March 2021. The data were analyzed through reduction, display, and conclusion. The results of the information research show that the social interactions that occur in people with COVID-19 sufferers are far from the cultural values ​​of the Indonesian people that have been going on so far. This can be caused by various factors such as incomplete public knowledge about COVID-19. Therefore, a local regional policy is needed to maximize the participation of community leaders such as the head of the local RT in providing complete information about COVID-19 to the people in their area. In addition, the role of the mass media is also needed in order to convey information to the wider community factually and reliably.